Industry view on the relative importance of "clonality" of biopharmaceutical-producing cell lines. Issue 2 (March 2016) - Frye, Christopher; Deshpande, Rohini; Estes, Scott; Francissen, Kathy; Joly, John; Lubiniecki, Anthony; Munro, Trent; Russell, Reb; Wang, Tongtong; Anderson, Karin
Abstract: Recently, several health authorities have requested substantial detail from sponsor firms regarding the practices employed to generate the production cell line for recombinant DNA-(rDNA) derived biopharmaceuticals. Two possible inferences from these regulatory agency questions are that (1) assurance of "clonality" of the production cell line is of major importance to assessing the safety and efficacy of the product and (2), without adequate proof of "clonality", additional studies of the cell line and product are often required to further ensure the product's purity and homogeneity. Here we address the topic of "clonality" in the broader context of product quality assurance by current technologies and practices, as well as discuss some of the relevant science and historical perspective. We agree that the clonal derivation of a production cell line is one factor with potential impact, but it is only one of many factors. Further, we believe that regulatory emphasis should be primarily placed on ensuring product quality of the material actually administered to patients, and on ensuring process consistency and implementing appropriate control strategies through the life cycle of the products.